PENGARUH TERAPI OKUPASI MENGGAMBAR TERHADAP TANDA DAN GEJALA HALUSINASI TAHAP COMFORTING PADA ORANG DENGAN GANGGUAN JIWA (ODGJ) DI RSJD Dr. ARIF ZAINUDDIN SURAKARTA - Syamsul Bahri, Ahmad; Lestari , Tri (Jurnal Kebidanan, 2024)
Background : Hallucinations are a symptom of mental disorders in humans which are characterized by changes in sensory perception, namely experiencing false sensations in the form of sound, sight, taste, touch or nose. The patient perceives stimuli that do not actually exist. One method of treatment is occupational drawing therapy, which is a form of psychotherapy that uses art as a communication tool. It is also a therapy that encourages a person to express, understand their feelings through artistic expression and creative processes, so that they can improve cognitive, affective and psychomotor functions.Objective : This research was conducted to determine whether there is an effect of occupational therapy drawing on the signs and symptoms of hallucinations in the comforting stage in ODGJ at RSJD Dr. Arif Zainuddin SurakartaMethod : This research uses a quantitative design using a pre-experimental design with a one group pre-test and post-test design. The sampling technique used is probability sampling with a total sample technique. In this study, the samples taken were 30 patients in three wards with hallucinatory disorders. With limited patients at RSJD Dr. Arif Zainuddin Surakarta, the researchers chose to use the total sample to avoid reducing the number of patients. Data collection using an observation sheet for signs and symptoms of hallucinations. The analysis used the Wilcoxon test.Results : Based on the results of the Wilcoxon test, the p-value was 0.000 (p < 0.05) or it could be said that the signs and symptoms of hallucinations had a p value smaller than the value of ? = 0.05, so Ha was accepted, meaning that there was an effect of providing occupational therapy on drawing on the signs and symptoms of hallucinations. symptoms of hallucinations in the comforting stage in ODGJ at RSJD Dr. Arif Zainuddin Surakarta.Conclusion : These results show that there is an effect of providing occupational drawing therapy on the signs and symptoms of hallucinations in the comforting stage in odgjd at RSJD Dr. Arif Zainuddin Surakarta Key words : hallucinations, drawing therapy